Intra Opertive Nausea And Vomiting (IONV) Pasca Pemberian Kombinasi Ondansetron dan Dexamethasone Menggunakan Teknik Spinal Anestesi - Andang Sudarmono; Ida Untari; Muhammad Nurfauzi (Lembaga Pengembangan Kinerja Dosen, 2024)
Spinal anesthesia is a procedure performed by injecting local anesthetic drugs into the subarachnoid block space and preventing the onset of excitatory nerve conduction by inhibiting ion flow. Intraoperative Nausea and Vomiting (IONV) is a common side effect after surgery and anesthesia. IONV is associated with various factors that can be categorized into risks related to patient factors, anesthetic factors, and surgical factors. Ondansetron is an oral and parenteral serotonin (5-HT3) receptor antagonist. It is used for the prevention and treatment of nausea and vomiting during chemotherapy, radiation therapy, and surgery. Ondansetron is a very safe and effective antiemetic compared to previous antiemetics. Dexamethasone is a class of steroids used as anti-inflammatory or immunosuppressive agents. Based on research it was found that dexamethasone can effectively prevent the occurrence of IONV. Objective: to assess the effectiveness of giving a combination of ondansetron and dexamethasone to prevent intraoperative nausea and vomiting with spinal anesthesia technique in IBS Simo Hospital. Research Methodology: the number of patients who have a history of DM makes it difficult to find respondents. The initial response plan of 44 people became 41 people. Results: Describe the characteristics consisting of gender, age, weight, ASA, and surgical diagnosis. Conclusion: Based on the results of research and discussion that has been done, it can be concluded that the average gender (51.2%), average age (39.0%), average Bb (53.7%), average ASA (75.6%), average duration of surgery (75.6%), and average IONV score analysis (95.1%).